Acute fatigue-induced changes in muscle mechanical properties and neuromuscular activity in elite handball players following a handball match - Thorlund, J. B.; Michalsik, L. B.; Madsen, K.; Aagaard, P. (Scandinavian Journal of Medicine & Science in Sports, 2008)
The purpose of the present study was to determine the acute fatigue development in muscle mechanical properties and neuromuscular activity in response to handball match play. Male elite handball players (n= 10) were tested before and after a simulated handball match for maximal isometric strength [maximal voluntary contraction (MVC)] and rate of force development (RFD) with synchronous electromyography (EMG) recording, while maximal vertical jump parameters were assessed using force plate analysis. Quadriceps and hamstrings MVC and RFD decreased significantly post-match (~10%, P<0.05 and ~16-21%, P<0.05, respectively). During quadriceps, MVC mean EMG amplitude [mean average voltage (MAV)] decreased for the vastus lateralis (VL) and rectus femoris (RF) (21-42%, P=0.05), while MAV also decreased in the antagonist biceps femoris (BF) muscle (48-55%, P<0.01). During hamstring MVC, MAV was reduced in BF (31%, P<0.01). Maximum EMG amplitude during quadriceps MVC was reduced for the VL (28%, P<0.01) and the RF (5%, P<0.05). During hamstring MVC, maximum EMG was reduced for BF (21%, P<0.01). Post-match maximal jump height was reduced (5.2%, P<0.01), as was also work (6.8%, P<0.01), velocity of center of mass (2.4-4.0%, P<0.01) and RFD (~30%, P<0.05). In conclusion, maximal (MVC) and rapid muscle force characteristics (RFD, impulse) were acutely affected concurrently with marked reductions in muscle EMG following handball match play, which may potentially lead to impaired functional performance.